HUBUNGAN SELF EFFICACY DENGAN PRESTASI BELAJAR SISWA KELAS V SD INPRES 12/79 PATTIRO SOMPE KECAMATAN SIBULUE KABUPATEN BONE - Hasman, Armitasari; Muin, Awaluddin; Sukaria, Muhammad Iksan (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This study is a quantitative research with a correlational research type that aims to determine whether there is a significant relationship between self efficacy and the learning achievement of fifth-grade students at SD Inpres 12/79 Pattiro Sompe, Sibulue District, Bone Regency. The research population consisted of 32 fifth-grade students, with a saturated sampling technique used. Data were collected using a questionnaire and documentation instruments. Data analysis techniques included descriptive statistical analysis and inferential statistical analysis. Based on descriptive statistical results, self-efficacy had an average score of 59.84 and a percentage of 74.84%, categorized as good, while student learning achievement had an average score of 80.59 and a percentage of 80.59%, also categorized as good. Based on inferential statistical analysis, the calculated t count (t_hitung) was 9.74, while the t table value (t_tabel) at a 5% significance level was 0,3494. Since t_count ≥ t_table, the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. This indicates that there is a significant positive relationship between self efficacy and the learning achievement of fifth-grade students at SD Inpres 12/79 Pattiro Sompe, Sibulue District, Bone Regency.